Sensational Internationalism The Paris Commune and the Remapping of American Memory in the Long Nineteenth Century - Coghlan, J. Michelle (Edinburgh University Press, 2016)
In refocusing attention on the Paris Commune as a key event in American political and cultural memory, Sensational Internationalism radically changes our understanding of the relationship between France and the United States in the long nineteenth century.